Flow‐Based Deacidification of Geobacter sulfurreducens Biofilms Depends on Nutrient Conditions: a Microfluidic Bioelectrochemical Study. Issue 23 (19th September 2018) - Zarabadi, Mir Pouyan; Charette, Steve J.; Greener, Jesse
Abstract: Biofilms from Geobacter sulfurreducens are promising materials for new bioelectrochemical systems. To improve the performance of such systems, limitations related to biofilm acidification should be addressed. This work examines a long‐held assumption that liquid flow can deacidify biofilm pH by enhancing molecular mass transport in the biofilm subdomain. A microfluidic electrochemical system was used to measure changes to biofilm pH in situ while accurately modulating hydrodynamic conditions under turnover, nutrient‐limited and starvation conditions. We discovered that increased flow rates could indeed mitigate biofilm acidification, but not under turnover concentrations, which are the predominant conditions used in research studies. This effect is demonstrated with the observation that relative increases to bio‐current under increased flow rates were stronger for experiments conducted under nutrient‐limited concentrations compared to turnover concentrations. This can open the way for a solution to poor performance of some bioelectrochemical systems at low concentrations. Abstract : Biofilms from Geobacter sulfurreducens are examined in a microfluidic electrochemical system. Changes to biofilm pH are measured in situ while modulating hydrodynamic turnover, nutrient‐limited and starvation conditions. Increased flow rates can mitigate biofilm acidification, but not under turnover concentrations. A relative increase to bio‐current under increased flow rates are stronger for experiments conducted under nutrient‐limited.